“EXACTLY WHAT I NEEDED FOR A GOOD NIGHT’S REST”: TRANSACTIONAL TINGLES AND ASMR AS EMERGING MEDIA GENRE - Maddox, Jessica (AoIR Selected Papers of Internet Research, 2020)
ASMR, or Autonomous Sensory Meridian Response, has become an international phenomenon. But what exactly ASMR is remains misunderstood. ASMR itself is a relatively new term, coined by scientists in 2010, but it describes an age-old feeling: the sensation of tingling on the scalp and spine. Biologically, it has been compared to fission or paresthesia. ASMRtists refer to this feeling as tingles. To this end, this research is informed by the results of a three-year long participant observation and ethnographic study in YouTube’s ASMR community in order to analyze ASMR as an emerging media genre. I argue ASMR is best understood as a genre, situated between the varying content possibilities of the text and the specific affordances of YouTube. By analyzing the relationship between platform governance, algorithms, monetization, care, and creativity, I identify a key component of the ASMR genre as transactional tingles. I define transactional tingles as the interaction between ASMRtist and viewer, in which the viewer receives a form of relaxation in exchange for clicks, likes, and views in the internet’s attention economy. , ASMR and transactional tingles have more in common with the artist/patron system of the Renaissance era or the Kickstarter campaigns of the twenty-first century, in which entertainers draw on their audiences for financial support. The culmination of my ethnography was the announcement of the ASMR app, Zees, which shows how creators harness the affordances of participatory culture to push the boundaries of genres while maintaining committed to the key principles for creator and viewer.